Evaluation of morphological relations between lower craniofacial skeletal structures and dimensions of upper respiratory tract in skeletal Classes I and III - Stelmańska, Karolina; Paluch, Zbigniew; Twardokęs, Marta; Ura-Sabat, Katarzyna; Frelich, Hanna; Szlęzak, Michał; Misiołek, Maciej (Journal of Stomatology, 2017)
Introduction. Review of the literature indicates the relationship between upper airways patency and lower jaw morphology. Aim of the study. To design multidimensional models to describe morphological relations of the linear and angular dimensions of hard tissues of the lower facial skeleton and the cervical spine (independent variables) with the linear dimensions of the upper respiratory tract (dependent variables). The obtained models took into consideration the age, gender and the skeletal Class I and III of the evaluated individuals. Material and method. The patients represented two skeletal classes: I (n = 97; 42.4%) and III (n = 53; 23.1%). Prior to orthodontic treatment, lateral cephalometric radiography (LCR) was performed in all patients. The obtained cephalometric measurements were evaluated statistically. Results. The statistical analysis pointed to significant differences between variables of the URT and dimensions of the facial skeleton and the cervical spine. It also revealed significant differences between variables of the URT and dimensions of the facial skeleton and the cervical spine. The independent variable Co-Gn emerged as an important predictor in regression of the nasopharynx. The anteroinferior height of the face and mandibular inclination were the factors relevant for oropharynx. Variables of the cervical spine were significant predictors in laryngopharyngeal models. Conclusions. The results illustrating morphological interrelations between the lower face and dimensions of the URT air space may prove helpful in planning orthodontic treatment, with or without teeth extraction, as well as orthognathic surgeries.